Coding relevance. (October 2022) - Macagno, Fabrizio
Abstract: Relevance is one of the crucial criteria for assessing the quality of argumentation in education. In argumentation and education, relevance has never been analyzed or coded. While several theories have included in their analysis some indicators of cohesion or clarity, this characteristic of dialogue and discourse has never been addressed as a distinct phenomenon. This paper builds on the existing studies in linguistic and philosophy to advance criteria for assessing relevance, which in turn can be used for developing a coding scheme for evaluating dialogue moves. Relevance is analyzed starting from the pragmatic principle that dialogue moves are instruments for pursuing a common dialogical goal. Starting from a classification of the possible types of dialogue moves, defined based on the possible dialogue that they propose or continue, five criteria of relevance are illustrated, capturing both pragmatic and topical coherence. Such criteria are shown to provide guidance for distinguishing not only relevant from irrelevant moves, but also the degrees of strength of relevance. The theoretical framework and the assessment criteria will be illustrated through a corpus of classroom interactions collected in Portuguese middle-grade schools.